Crisis in the schools : crisis, crisis intervention training, and school counselor burnout - Morris, Carrie A. Wachter (2006)
"In the course of a school year, schools may face a number of crisis situations, including suicidality, child abuse and neglect, violence, and natural disasters that may impact individual students or create school-wide crises (Collins & Collins, 2005; Mathai, 2002). Each of these crises can pose a threat to student and school safety and, therefore, requires swift and precise action. In addition to the potential lethality of these situations, they also can take an emotional toll on school personnel, potentially leading to increased levels of burnout (Collins & Collins). Despite the prevalence of crisis situations in schools, there is a dearth of literature referencing school crisis intervention. To date, researchers have not considered important issues such as training in crisis intervention, adequacy of preparation, and self-perceived skills that are necessary to provide crisis intervention in the schools. Because schools serve as the primary provider of child and adolescent mental health services (Burns et al. 1995; Hoagwood & Erwin, 1997), limited training in crisis intervention may leave the professional school counselor less than adequately prepared for the crises they encounter in their schools (Allen et al., 2002). The current study examined the impact of crisis related issues (type, frequency, and training) on school counselor burnout in order to describe any potential links between level and perceived adequacy of training, perception of crisis intervention efficacy, frequency of crises encountered, self-perceived crisis intervention skills, and level of burnout experienced. Specifically, results indicated that school counselors worked with a variety of individual crisis situations multiple times during the previous year, but may have gaps in their training experiences regarding crisis topics. On average, participants found crisis training helpful, and some types of crisis training were negatively correlated with levels of burnout. Findings of this study may inform further research on the potential relationships between crisis training, crisis frequency, and school counselor burnout. Counselor educators and school counselors may use these findings to explore ways to best prepare school counselors for crisis intervention. This exploration may ultimately help current and future school counselors both provide effective crisis intervention and prevent their own burnout."--Abstract from author supplied metadata